The Effectiveness of Learning with the Team Based Project Method in the Decision Making Technique Course by Using the Product Oriented Module - Wijaya, Kinanti; Siregar, Syafiatun; Sutrisno; Yuzni, Siti Zulfa; Sari, Ruri Aditya; Idris, Iswandi; Ramadani (JTP - Jurnal Teknologi Pendidikan, 2021)
The purpose of this study is (a) to identify learning using the team-based project method implemented in practical courses using product-oriented modules in vocational education. (b) to know the level of effectiveness of learning with the team-based project method implemented in practical courses using a product-oriented module in Vocational Education. This study used research related to this study, which were all students who were taking the Decision-Making Technique course. The number of research samples was 60 people (2 classes) of the 2018 Business Administration study program as a field test, 9 people as a small group test and 3 people for an individual test. The results showed that from the material expert, 4 aspects were assessed in the material expert test, namely the material aspect, the quiz question aspect, the linguistic aspect and the implementation aspect. The material aspect has a higher percentage value than the other three aspects, namely 85.45%, then the questions and quiz aspects and the implementation aspect have 80%, while the linguistic aspect has 60%. With this percentage value, the overall assessment of the material experts assesses that this learning media was considered "Eligible" to be developed. Based on the results of the t-test calculations, data obtained that tcount> ttable or 5,868> 2,0172 or in other words H0 is rejected and Ha is accepted, it can be concluded that the learning outcomes using Learning Methods of Team Based Learning on practice course with Product-Oriented Module was higher than students who were taught without using Learning Method of Team Based Learning In practical courses with Product-Oriented Modules with the effectiveness of using Learning Methods of Team Based Learning In practical courses with Product-Oriented Modules of 88,5667% .